FRAMEWORK OF A LIGHTWEIGHT BLOCKCHAIN-BASED MODEL FOR SECURE INTERNET OF MEDICAL THINGS (IOMT) DATA MANAGEMENT. - Obiniyi, Afolayan Ayodele; Oloruntoba, Leke Joseph (FUDMA Journal of Sciences, 2026)
The widespread adoption of the Internet of Medical Things (IoMT) is the main factor that brought about big changes in the healthcare system but also at the same time made the system struggle with major issues like data breaches, device incompatibility, scalability problems, delays, and cyber security risks. The conventional security procedures and central cloud storage systems are always limited if one looks at the throughput, cost of implementation, and failure points along with threats to security that are associated with them. This research proposed a lightweight blockchain-based system for the protection of IoMT data while concurrently tackling the issues of performance and scalability. The proposed system consists of six interconnected layers: IoMT device layer, lightweight encryption layer, interoperability layer, lightweight consensus layer, blockchain network layer, and the InterPlanetary File System (IPFS) storage layer. In this architecture, IPFS has been picked as a replacement for traditional cloud storage with an intention to allow decentralized, tamper-proof, and efficient management of medical data. A lightweight consensus mechanism which is specifically designed for IoMT devices that consume low power and are resource constrained is incorporated into the system to bring down transaction processing overhead and at the same time raise system responsiveness. The proposed framework provides a high level of throughput with a low latency when executing transactions ranging from 50 transactions to 5000 transactions.
Keywords: Internet of Medical Things (IoMT); Blockchain technology; Interoperability; Data security; Consensus mechanism; Lightweight cryptography